Physiologic Effects of Intra-nasal Sedation with Midazolam and Ketamine in 3-6 Years old Uncooperative Children - Mehran, Majid; Tavassoli-Hojjati, Sara; Ameli, Nazila; Salehi Zeinabadi, Mehdi (Journal of Dental School, 2019)
Objective: Several medications have been used for sedation in children in dentistry and intra-nasal route has been reported to be an efficient way regarding patient cooperation. The aim of the present study was to compare the changes in physiologic parameters following intra-nasal midazolam and ketamine administration. Methods: In this randomized cross-over double-blind trial, 17 uncooperative 3-6 years old children requiring at least two dental treatments were selected randomly and received intra-nasal ketamine (0.5 mg/kg) and midazolam (0.2 mg/kg) prior to the treatment using the other drug in the next visit. Physiologic parameters including blood pressure, heart rate, respiratory rate and O2 saturation were measured and compared during the different time intervals using two way repeated measure ANOVA. Results: The patients showed higher blood pressure and heart rate following ketamine administration compared to midazolam (p<0.001). No significant difference was found between the drugs at different time intervals regarding respiratory rate and O2 saturation. (p>0.05) Conclusion: In spite of significant differences between midazolam and ketamine regarding heart rate and blood pressure, both drugs can b e used as effective sedative medications without treatment interruption in children.